Deep eutectic solvent on extraction of flavonoid glycosides from Dendrobium officinale and rapid identification with UPLC-triple-TOF/MS. (1st February 2023) - Sui, Minghui; Feng, Simin; Liu, Gaodan; Chen, Bilian; Li, Zhenhao; Shao, Ping
Highlights: The yield of flavonoids was significantly increased by using Chol-Lac. Hydrogen bonds in DESs were considered to be the key to the extraction differences. Fourteen flavonoid glycosides were rapidly identified by UPLC-Triple-TOF/MS. The extraction yield of flavonoid glycosides varied greatly with different DESs. Abstract: In this study, ultrasonic-assisted deep eutectic solvent (DES) method was used to extract flavonoids from Dendrobium officinale . The mechanism of DESs extraction differences was investigated by physicochemical characterization and molecular dynamics simulation experiments. Moreover, flavonoids from Dendrobium officinale were rapidly identified and quantitatively analyzed by UPLC-Triple-TOF/MS without removing DES. The results showed choline chloride-lactic acid (Chol-Lac) had the best extraction effect among forty groups of DESs, the extraction yield was up to 35.23 ± 2.12 mg/g. It was speculated that the tight hydrogen bond structure was the key to the better extraction ability of Chol-Lac. Meanwhile, the viscosity was the main physical parameter reflecting the hydrogen bond structure of DES. Fourteen flavonoid glycosides were identified, among which the content of rutin (1.94 ± 0.24 mg/g) was the highest. And the results of cluster analysis showed that different DESs had great differences in the extraction of flavonoid glycosides.